2021
DOI: 10.1016/j.foodchem.2020.127726
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the malaxation temperature on the phenolic profile of cv. Cobrançosa olive oils and assessment of the related health claim

Abstract: Phenolic compounds contribute to the bioactive properties of olive oil. However, olive oils can only support a health claim concerning the protection against oxidative stress depending on the polyphenolic concentration, requiring effective measures during extraction to preserve/enhance their concentrations. The effect of the malaxation temperature (22, 28 and 34°C) on the phenolic profile was studied for industrially extracted cv. Cobrançosa oils. Higher malaxation temperatures decreased the contents of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…Indeed, β values of the total secoiridoids were −8.00 and −18.25 when the temperature was increased to 25 and 30 °C, respectively, and −8.15 when malaxation was extended from 30 to 45 min ( Table 3 ). Studies show that secoiridoids are the phenolic group most affected by oxidative degradation [ 27 ] and temperature [ 6 ]. A depletion of secoiridoids with malaxation time and temperature has been attributed to the action of oxidoreductases [ 4 , 14 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, β values of the total secoiridoids were −8.00 and −18.25 when the temperature was increased to 25 and 30 °C, respectively, and −8.15 when malaxation was extended from 30 to 45 min ( Table 3 ). Studies show that secoiridoids are the phenolic group most affected by oxidative degradation [ 27 ] and temperature [ 6 ]. A depletion of secoiridoids with malaxation time and temperature has been attributed to the action of oxidoreductases [ 4 , 14 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results in the literature are contradictory. Marx, Casal et al [ 6 ] observed an increase in flavones with temperature, but no trend for phenolic alcohols and acids, whereas other studies found no changes in the flavone content [ 14 , 33 ]. Boselli et al [ 31 ] reported that phenolic acids and alcohols were not significantly affected by malaxation temperature and time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenolic profile of the olive oil samples was established following the guidelines of the International Olive Council (IOC) [30], with minor modifications as previously described [9]. Methanolic extracts (80% v/v), from duplicate extractions of each sample, were injected in a HPLC-DAD system (Jasco, Japan) comprising a data transmitter (LC-NetII/ADC), two integrated pumps (PU-4180), an auto-sampler (AS-4050), a column oven (ECOM Eco2000, Czech Republic), and the DAD (MD-4010).…”
Section: Phenolic Compounds Profilementioning
confidence: 99%
“…Several strategies have been proposed to enhance the phenolics contents of olive oils, namely the optimization of the extraction conditions (e.g., malaxation/extraction time-temperature conditions during malaxation [8][9][10]). Another trend focused on the use of natural sources such as olive oil by-products, namely olive leaves [11].…”
Section: Introductionmentioning
confidence: 99%